Optimization of fermentation conditions for the expression of interleukin-3 in fusion with pelb in E. coli - Huong, Duong Thu; Quy, Nguyen Thi; Ngoc Ha, Dang Thi; Thu Hong, Le Thi; Hai, Truong Nam (Academia Journal of Biology, 2016)
Interleukin-3 (IL-3) is a multifunctional cytokine which modulates the proliferation, differentiation and maturation of various types of hematopoietic cells. Gene coding for IL-3 linked with pelB signal were incorporated into pET22b(+) for  expression of il3 gene in E. coli BL21; but IL-3 was synthesized at very low levels and still in fusion with PelB. To facilitate purification process, finding the appropriate fermentation conditions plays a key role in order to enhance gene il-3 expression and cleavage of PelB. In this study, we have optimized the conditions for the expression of IL-3, which included E. coli host strain JM109, LB cultivation medium, induction temperature was 25oC; induction with 0.05 mM IPTG at OD600 = 1. The cell biomass increases at about 2.3 times after optimization. IL-3 protein was expressed in the form of inclusion body and the PelB signal was cleaved. This result is conducive for purification of large amount of IL-3 to determine characteristics of protein.